Silicon-based composite material and preparation method thereof
By forming in situ and connecting nanosilicon particles in a porous carbon substrate, the problem of volume expansion of silicon-based anode material is solved, the strength and cycle stability of the composite material are improved, and it is suitable for industrial production.
Patent Information
- Application Number
- CN202310967011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
The volume expansion of the silicon-based negative electrode material during the deintercalation of lithium is severe, resulting in damage to the electrode structure, decay of battery capacity and reduced cycle stability, limiting its industrial application.
A silicon-based composite material is used to form nanosilicon particles and SiOx particles in situ in the pores of the porous carbon substrate, and connect the carbon-containing substrate with the silicon-containing particles through chemical bonds to improve the strength and cycle stability of the composite material.
It effectively prevents structural damage caused by expansion of lithium embedded silicon, improves the cycle stability and dynamic performance of composite materials, and is suitable for large-scale industrial production.
Smart Images

Figure CN119447206A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a silicon-based composite material and a preparation method thereof. Background Art
[0002] In recent years, with the rapid popularization and development of portable electronic devices, electric vehicles, etc., traditional graphite negative electrodes can no longer meet the current market demand for high energy density and long cycle life, and there is an urgent need to find the next generation of lithium-ion battery negative electrode materials.
[0003] Compared with carbon-based negative electrode materials, silicon is an alloyed lithium-intercalation material with a theoretical lithium-intercalation capacity of up to 4200mAh / g. It is also abundant in resources, safe and non-toxic, and is the most promising negative electrode material for lithium-ion batteries. However, silicon will undergo a huge volume expansion of up to about 300% during the process of lithium intercalation and deintercalation, which will have the following adverse effects: silicon particles will pulverize, lose electrical contact, electrode structure will be destroyed, and the SEI film will repeatedly undergo "formation-destruction-reformation", resulting in battery capacity decay, reduced coulombic efficiency, and decreased cycle stability.
[0004] To solve the problem of silicon expansion, a variety of solutions have been proposed, such as optimizing the size of silicon materials, regulating the structure of silicon nanomaterials, or compounding silicon with different materials. The volume expansion of silicon-based negative electrode materials such as silicon-oxygen negative electrode materials has been greatly reduced, but this improvement is far from enough for practical applications. The volume expansion of silicon is still the biggest problem restricting the industrial application of silicon-based negative electrode materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a silicon-based composite material to solve the problem of volume expansion of silicon-based negative electrode materials in the prior art. At the same time, chemical bonds are formed between the elements in the composite material, thereby improving the strength of the composite material and preventing the expansion of lithium-embedded silicon from causing structural damage to the composite material.
[0007] A second object of the present invention is to provide a method for preparing a silicon-based composite material.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The first aspect of the present invention provides a silicon-based composite material, comprising a carbon-containing substrate and silicon-containing particles; the carbon-containing substrate comprises a porous carbon substrate or a porous carbon substrate doped with a first doping element M; the silicon-containing particles comprise nano-silicon particles and SiO xParticles, where 0 < x ≤ 2; alternatively, the silicon-containing particles include nano-silicon particles and at least partially surface-oxidized nano-silicon particles; the silicon-containing particles are dispersed in the pores of the porous carbon substrate; at least part of the carbon-containing substrate and the silicon-containing particles form at least one of the bonds C-Si, C-O-Si, C-M-Si, C-O-M-Si, C-O-M-O-Si, C-M-O-Si.
[0010] Further, the first doping element M includes at least one of Li, Al, Mg, Ca, Ba, Mn, Fe, Co, Ni, Cu, Zr, Mo, Ge, Sn, Zn, Ti, B, P, S, and N.
[0011] Further, the silicon-containing particles further include a second doping element R, and the second doping element R includes at least one of N, P, S, C, H, Li, Al, and Mg; at least part of the second doping element R forms at least one of the bonds Si-R, Si-O-R, and Si-R-O with the silicon atoms in the silicon-containing particles.
[0012] Further, the pore volume of the silicon-based composite material is 0.001 cm 3 / g - 0.2 cm 3 / g, and the specific surface area is 0.1 m 2 / g - 50 m 2 / g.
[0013] Further, based on 100% of the mass of the silicon-based composite material, the proportion of silicon element is 10 wt.% - 80 wt.%, the proportion of oxygen element is 0 wt.% - 10 wt.%, and the total proportion of the first doping element M and the second doping element R is 0 wt.% - 10 wt.%.
[0014] Further, the porous structure of the porous carbon substrate is a continuous dendritic through-hole.
[0015] Preferably, the pore diameter of the porous structure is larger than the particle size of the silicon-containing particles.
[0016] Preferably, the pore diameter of the porous structure is 0.5 nm - 50 nm.
[0017] Preferably, the particle size of the silicon-containing particles is 0.5 nm - 20 nm.
[0018] Further, the silicon-based composite material further includes a coating layer, and the material of the coating layer includes an ion-conducting material and / or an electron-conducting material.
[0019] Preferably, the ion-conducting material includes at least one of a LISICON-type solid electrolyte, a NASICION-type solid electrolyte, a perovskite-type solid electrolyte, a garnet-type solid electrolyte, a sulfide solid electrolyte and a PEO-based polymer electrolyte.
[0020] Preferably, the conductive electronic material includes at least one of soft carbon, hard carbon, carbon black, graphite, graphene, carbon nanotubes, and carbon fibers.
[0021] Furthermore, the silicon-based composite material also includes at least one of lithium silicate, magnesium silicate, aluminum silicate, lithium aluminum silicate, lithium magnesium silicate and magnesium aluminum silicate.
[0022] The second aspect of the present invention provides a method for preparing the silicon-based composite material, using an inert gas as a carrier gas, introducing a silicon-containing precursor and an oxygen-containing precursor, and using vapor deposition to load silicon-containing particles in the pores of the carbon-containing substrate.
[0023] Preferably, the step further comprises doping the carbon-containing substrate with a first element M.
[0024] Preferably, the step further comprises doping the silicon-containing particles with a second element R.
[0025] Preferably, the step further comprises coating the surface of the silicon-based composite material with an ion-conducting material and / or an electron-conducting material.
[0026] Furthermore, the temperature of the vapor deposition is 150° C.-1000° C., and the time is 0.1 h-100 h.
[0027] Preferably, the silicon-containing precursor includes at least one of monosilane, disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives.
[0028] Preferably, the oxygen-containing precursor comprises at least one of oxygen, carbon dioxide, water vapor, methanol, ethanol, n-propanol, isopropanol, butanol, acetone and butanone.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] In the silicon-based composite material provided by the present invention, silicon-containing particles are formed in situ in the porous structure of the carbon-containing substrate, and the carbon-containing substrate and the silicon-containing particles are connected by chemical bonds, thereby improving the strength of the composite material, preventing the expansion of lithium-embedded silicon from causing structural damage to the composite material, and improving the cycle stability of the composite material; in addition, the connection of chemical bonds is conducive to the transmission of lithium ions (electrons), which can prevent silicon from losing contact with the carbon-containing substrate after multiple charge and discharge cycles, thereby improving the dynamic performance.
[0031] The preparation method provided by the present invention features continuous process, high degree of mechanization, strong controllability, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0033] Figure 1 SEM image of the silicon-based composite material obtained in Example 1;
[0034] Figure 2 XPS image of the silicon-based composite material obtained in Example 1;
[0035] Figure 3 Mapping image of the silicon-based composite material obtained in Example 1. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0036] The following will describe in detail the implementation schemes of the present invention in combination with the embodiments and examples. However, those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present invention.
[0037] The first aspect of the present invention provides a silicon-based composite material, comprising a carbon-containing substrate and silicon-containing particles; the carbon-containing substrate comprises a porous carbon substrate or a porous carbon substrate doped with a first doping element M; the silicon-containing particles comprise nano-silicon particles and SiO x particles, where 0 < x ≤ 2; alternatively, the silicon-containing particles comprise nano-silicon particles and at least partially surface-oxidized nano-silicon particles; the silicon-containing particles are dispersed in the pores of the porous carbon substrate; at least a part of the carbon-containing substrate and the silicon-containing particles form at least one of the bonds C-Si, C-O-Si, C-M-Si, C-O-M-Si, C-O-M-O-Si, C-M-O-Si.
[0038] Further, the first doping element M comprises at least one of Li, Al, Mg, Ca, Ba, Mn, Fe, Co, Ni, Cu, Zr, Mo, Ge, Sn, Zn, Ti, B, P, S, and N.
[0039] Furthermore, the silicon-containing particles further include a second doping element R, and the second doping element R includes at least one of N, P, S, C, H, Li, Al and Mg; at least part of the second doping element R forms at least one of Si-R, Si-OR and Si-RO bonds with silicon atoms in the silicon-containing particles. The chemical bond formed by the silicon element and the second doping element R is preferably Si-O, Si-H, Si-OH, Si-NO.
[0040] In the silicon-based composite material provided by the present invention, silicon-containing particles are formed in situ in the porous structure of the carbon-containing substrate, and the carbon-containing substrate and the silicon-containing particles are connected by chemical bonds, thereby improving the strength of the composite material, preventing the expansion of lithium-embedded silicon from causing structural damage to the composite material, and improving the cycle stability of the composite material; in addition, the connection of chemical bonds is conducive to the transmission of lithium ions (electrons), which can prevent silicon from losing contact with the carbon-containing substrate after multiple charge and discharge cycles, thereby improving the dynamic performance.
[0041] The chemical bonding formed by at least part of the carbon-containing substrate and the silicon-containing particles, on the one hand, shortens the transmission distance of the active ions, reduces the interlayer ion diffusion transmission resistance, and improves the fast charging performance of the silicon-based composite material; on the other hand, the first doping element M bonds the Si and C atoms, increases the active ion binding and storage sites, and improves the specific capacity of the silicon-based composite material.
[0042] Furthermore, the pore volume of the silicon-based composite material is 0.001 cm 3 / g-0.2cm 3 / g, specific surface area is 0.1m 2 / g-50m 2 / g.
[0043] Typically, but not limiting, the pore volume of silicon-based composites is 0.001 cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g, 0.15cm 3 / g or 0.2cm 3 / g.
[0044] Typically, but not limiting, the surface area of silicon-based composite materials is 0.1 m 2 / g, 0.5m 2 / g, 1m 2 / g, 10m 2 / g, 20m 2 / g, 40m 2 / g or 50m 2 / g.
[0045] Furthermore, based on 100% by mass of the silicon-based composite material, the proportion of silicon element is 10wt.%-80wt.%, the proportion of oxygen element is 0wt.%-10wt.%, and the proportion of the first doping element M and the second doping element R is 0wt.%-10wt.% in total.
[0046] Furthermore, the porous structure of the porous carbon substrate is continuous branch-like through holes; the silicon-containing particles are dispersed in the branch-like through holes of the carbon-containing substrate, which is conducive to the uniform dispersion of the silicon-containing particles in the carbon-containing substrate and avoids the aggregation of silicon-containing particles leading to uneven expansion of the composite material during the lithium insertion / extraction process.
[0047] Preferably, the pore size of the porous structure is larger than the particle size of the silicon-containing particles, providing a buffer space for the silicon-containing particles to expand.
[0048] Preferably, the pore size of the porous structure is 0.5 nm-50 nm; typically but not limiting, the pore size of the porous structure is 0.5 nm, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.
[0049] Preferably, the particle size of the silicon-containing particles is 0.5 nm to 20 nm. Typically, but not limiting, the particle size of the silicon-containing particles is 0.5 nm, 1 nm, 5 nm, 10 nm, 12 nm, 14 nm, 17 nm or 20 nm.
[0050] Furthermore, the silicon-based composite material also includes a coating layer, the material of the coating layer includes ion-conducting material and / or electronically conductive material, which can improve the ion-conducting and / or electronically conductive ability of the composite material and improve the rate performance of the composite material electrode.
[0051] Preferably, the ion-conducting material includes at least one of a LISICON-type solid electrolyte, a NASICION-type solid electrolyte, a perovskite-type solid electrolyte, a garnet-type solid electrolyte, a sulfide solid electrolyte and a PEO-based polymer electrolyte.
[0052] Preferably, the conductive electronic material includes at least one of soft carbon, hard carbon, carbon black, graphite, graphene, carbon nanotubes, and carbon fibers.
[0053] Furthermore, the silicon-based composite material also includes at least one of lithium silicate, magnesium silicate, aluminum silicate, lithium aluminum silicate, lithium magnesium silicate and magnesium aluminum silicate.
[0054] The second aspect of the present invention provides a method for preparing the silicon-based composite material, which is characterized in that an inert gas is used as a carrier gas, a silicon precursor and an oxygen-containing precursor are introduced, and silicon-containing particles are loaded into the pores of the carbon-containing substrate by chemical vapor deposition.
[0055] The preparation method provided by the present invention has continuous process, high degree of mechanization, strong controllability and is suitable for large-scale industrial production.
[0056] The carbon-containing substrate includes a porous carbon substrate or a porous carbon substrate doped with a first doping element M. In some embodiments, the porous carbon substrate can be prepared by pyrolysis and / or activation of a carbon precursor (such as a polymer precursor, a biomass precursor, and a fossil carbon source). Preferably, the step further includes doping the carbon-containing substrate with the first element M. As known to those skilled in the art, a porous carbon substrate doped with the first element M can be obtained by introducing a precursor containing the element M during the preparation process, and the specific doping method is not described in detail in this application.
[0057] Furthermore, the temperature of the chemical vapor deposition is 150°C - 1000°C, and the time is 0.1 h - 100 h.
[0058] Preferably, the silicon precursor includes at least one of silane, disilane, trisilane, halogenated silane, polysilane, silafluorene and its derivatives, and silole and its derivatives.
[0059] Preferably, the oxygen-containing precursor includes at least one of oxygen, carbon dioxide, water vapor, methanol, ethanol, n-propanol, isopropanol, butanol, acetone and butanone. During the silicon deposition process, introducing the oxygen-containing precursor can form SiO x particles (0 < x ≤ 2) in the porous structure of the carbon-containing substrate, or form an oxide layer on the surface of the in-situ formed nano-silicon particles.
[0060] Preferably, the step further includes doping the silicon-containing particles with a second element R. When introducing a mixed gas of the silicon precursor and the oxygen-containing precursor, a precursor containing the element R, such as an N-containing precursor, a P-containing precursor, an S-containing precursor, a C-containing precursor, can be introduced simultaneously; alternatively, the vapor of the element R, such as metal Li vapor and metal Mg vapor, can be introduced simultaneously, so as to dope the second element R into the silicon-containing particles.
[0061] Preferably, the step further includes coating an ion-conducting material and / or an electron-conducting material on the surface of the silicon-based composite material. The surface coating adopts common coating means in the art, such as chemical vapor deposition (CVD) coating, atomic layer deposition (ALD) coating, sol-gel coating or hydrothermal / solvothermal coating, etc., and the specific steps are not described in detail in this application.
[0062] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0063] Example 1
[0064] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0065] 1. Raise the temperature of sucrose to 800°C at 2°C / min in a N2 atmosphere and keep it for 2 h. Raise the temperature to 900°C in a 20% CO2-N2 mixed gas and keep it for 2 h. Crush and grade the obtained material to obtain porous carbon.
[0066] 2. After the porous carbon is heated from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere, it is changed to a 20% SiH4-N2 mixed gas; in the 20% SiH4-N2 mixed gas atmosphere, it is kept at 600°C for 2 hours to deposit silicon; then it is changed to N2, cooled to 200°C, and then changed to a 1% O2-N2 mixed gas; in a 1% O2-N2 mixed gas atmosphere, it is kept at 200°C for 12 minutes for oxygen-containing treatment; then it is changed to N2 and heated to 600°C, and silicon deposition-oxygen-containing treatment cycles are carried out on the porous carbon for 15 times, and the temperature is naturally cooled under the protection of N2; crushing and grading are carried out to obtain a silicon-based composite material semi-finished product.
[0067] 3. The semi-finished silicon-based composite material was heated to 800°C at 2°C / min in a N2 atmosphere and kept in a 50% C2H2-N2 mixed gas for 0.5 h to obtain a carbon coating layer with a thickness of 10 nm. The silicon-based composite material was obtained, and its SEM image is shown as follows: Figure 1 shown. Figure 2 This is the XPS curve of the silicon-based composite material prepared in this example, and it can be seen that the silicon atoms and carbon atoms are bonded by chemical bonds. Figure 3 This is a mapping diagram, which shows that the elements C, O, and Si are evenly distributed.
[0068] Example 2
[0069] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0070] 1. After sucrose and melamine are mixed and ground, the temperature is increased to 800°C at 2°C / min in a N2 atmosphere and maintained for 5 h. The temperature is increased to 900°C in water vapor and maintained for 2 h. The obtained material is crushed and graded to obtain N-doped porous carbon.
[0071] 2. Same as Example 1.
[0072] 3. Same as Example 1.
[0073] Example 3
[0074] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0075] 1. After mixing and grinding cellulose and phytic acid, the temperature was raised to 800°C at 2°C / min in a N2 atmosphere and maintained for 2 h. The obtained material was crushed and graded, mixed with KOH at a mass ratio of 5:1, and activated at 800°C for 2 h to obtain P-doped porous carbon.
[0076] 2. Same as Example 1.
[0077] 3. Same as Example 1.
[0078] Example 4
[0079] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0080] 1. Same as Example 1.
[0081] 2. Use a mixed gas of 20% SiH4-N2 and metallic lithium vapor to replace the 20% SiH4-N2 in Example 1. The remaining raw materials and methods are the same as those in step 2 of Example 1.
[0082] 3. Same as Example 1.
[0083] Example 5
[0084] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0085] 1. Same as Example 1.
[0086] 2. Use a mixture of 20% SiH4-N2 and metallic magnesium vapor to replace the 20% SiH4-N2 in Example 1. The remaining raw materials and methods are the same as those in step 2 of Example 1.
[0087] 3. Same as Example 1.
[0088] Example 6
[0089] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0090] 1. After mixing and grinding sucrose and magnesium oxide, the temperature was raised to 800°C at 2°C / min in a N2 atmosphere and maintained for 5 h. The temperature was raised to 900°C in water vapor and maintained for 2 h. The obtained material was crushed and graded to obtain Mg-doped porous carbon.
[0091] 2. Use a mixed gas of 15% SiH4-N2 and urea to replace the 20% SiH4-N2 in Example 1. The remaining raw materials and methods are the same as those in step 2 of Example 1.
[0092] 3. Same as Example 1.
[0093] Example 7
[0094] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0095] 1. After mixing and grinding sucrose and alumina, the mixture was heated to 800°C at 2°C / min in a N2 atmosphere and maintained for 5 h. The mixture was heated to 900°C in water vapor and maintained for 2 h. The obtained material was crushed and graded to obtain Al-doped porous carbon.
[0096] 2. Use a mixed gas of 15% SiH4-N2 and boric acid to replace the 20% SiH4-N2 in Example 1. The rest of the raw materials and methods are the same as in step 2 of Example 1.
[0097] 3. Same as Example 1.
[0098] Example 8
[0099] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0100] 1. After sucrose and melamine are mixed and ground, the temperature is increased to 800°C at 2°C / min in a N2 atmosphere and maintained for 5 h. The temperature is increased to 900°C in water vapor and maintained for 2 h. The obtained material is crushed and graded to obtain N-doped porous carbon.
[0101] 2. Use a mixed gas of 15% SiH4-N2 and urea to replace the 20% SiH4-N2 in Example 1. The remaining raw materials and methods are the same as those in step 2 of Example 1.
[0102] 3. Same as Example 1.
[0103] Example 9
[0104] This embodiment provides a silicon-based composite material, and the specific preparation process is as follows:
[0105] 1. Same as Example 6.
[0106] 2. Same as Example 6.
[0107] 3. Disperse the semi-finished particles of the silicon-based composite material in a 5% Al(NO3)3 aqueous solution, ultrasonically stir and filter the excess liquid, dry in an oven at 80°C, and sinter at 400°C in a N2 atmosphere for 2 hours to obtain an Al2O3-coated nano-silicon-carbon composite material with an Al2O3 coating layer of 10 nm thickness, thereby obtaining a silicon-based composite material.
[0108] Comparative Example 1
[0109] This comparative example provides a silicon-based composite material, and the specific preparation method is as follows:
[0110] 1. Mix silicon powder and sodium dodecyl sulfate, then add anhydrous ethanol, and obtain nano silicon slurry with a particle size of 50 to 100 nm by sand grinding.
[0111] 2. Add the carbon-containing substrate obtained in step 1 of Example 1 into the nano-silicon slurry, mix well and then spray-dry to obtain a semi-finished silicon-based composite material.
[0112] 3. Same as Example 1.
[0113] Test Case
[0114] The element contents of the silicon-based composite materials provided in Examples 1-9 and Comparative Example 1 were measured using an inductively coupled plasma spectrometer.
[0115] The silicon-based composite materials provided in Examples 1-9 and Comparative Example 1 were used to prepare negative electrode sheets, and the negative electrode sheets were used to prepare CR2032 button batteries using conventional methods, and the batteries were tested for electrical properties. The specific test method is:
[0116] (1) Half-cell assembly: CR2032 button cells were assembled in a glove box, with lithium metal sheets as counter electrodes, polypropylene microporous membranes as separators, and the electrolyte being LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC = 1:1), where the LiPF6 concentration was 1 mol / L.
[0117] The battery is charged and discharged using the LAND battery testing system.
[0118] (2) Gram capacity, first efficiency and capacity retention rate test: After the CR2032 battery is left standing for 6 hours, it is discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V; after standing for 5 minutes, it is charged to 1.5V at a constant current of 0.05C; the first lithium removal gram capacity is the gram capacity (or mass specific capacity) of the electrode material, and the ratio of the first lithium removal capacity to the first lithium insertion capacity is the first coulombic efficiency of the battery. Continue to discharge at 0.05C to 0.005V, and then discharge at 0.01C to 0.005V; after standing for 5 minutes, it is charged to 1.5V at a constant current of 0.05C, and repeat the charge and discharge 50 times. The lithium removal capacity of the 50th cycle / the lithium removal capacity of the first cycle × 100% is calculated to obtain the capacity retention rate.
[0119] Material compaction density test: The powder density of the negative electrode material particles prepared in Example and Comparative Example 1 was measured, and the pressure was maintained at 1t for 10s to obtain compaction density test data.
[0120] The test results of various embodiments and comparative examples are shown in Table 1 below.
[0121] Table 1 Test results of various embodiments and comparative examples
[0122]
[0123] Examples 1 to 9 are silicon-based negative electrode materials grown in situ by CVD, where silicon atoms and carbon atoms are chemically bonded. Comparative Example 1 is a silicon-based composite material prepared by physical mixing, where silicon atoms and carbon atoms exist alone. As shown in Table 1, the compaction density and cycle performance of the silicon-based negative electrode material grown in situ by CVD are better than those of the silicon-based negative electrode material physically mixed by ball milling in Comparative Example 1, because the in-situ growth mechanism allows the elements to be chemically bonded, and the chemical bonds have higher bond energy, so the material strength is higher, thereby having better cycle performance. The addition of doping elements can buffer the expansion of silicon atoms on the one hand, and on the other hand, it can strengthen the chemical bonds and improve the structural strength. It can be seen that the dual-doped silicon-based composite material has a higher compaction density and better cycle performance than the single-doped material. Examples 4 and 5 are metal doped, and finally exist in the form of metal silicates, which capture some oxygen atoms and reduce the irreversible capacity, so the first coulomb efficiency is higher than that of other examples.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A silicon-based composite material, characterized in that: including a carbon-containing substrate and silicon-containing particles; The carbon-containing substrate includes a porous carbon substrate or a porous carbon substrate doped with a first doping element M; The silicon-containing particles include nano-silicon particles and SiO x particles, where 0 < x ≤ 2; alternatively, the silicon-containing particles include nano-silicon particles and at least partially surface-oxidized nano-silicon particles; The silicon-containing particles are dispersed in the pores of the porous carbon substrate; At least a portion of the carbon-containing substrate and the silicon-containing particles form at least one bond selected from the group consisting of C—Si, CO—Si, CM-Si, COM-Si, COMO-Si, and CMO-Si.
2. The silicon-based composite material according to claim 1, characterized in that: The first doping element M includes at least one of Li, Al, Mg, Ca, Ba, Mn, Fe, Co, Ni, Cu, Zr, Mo, Ge, Sn, Zn, Ti, B, P, S and N.
3. The silicon-based composite material according to claim 1 or 2, characterized in that: The silicon-containing particles further include a second doping element R, wherein the second doping element R includes at least one of N, P, S, C, H, Li, Al and Mg; At least a portion of the second doping element R forms at least one of Si-R, Si-OR and Si-RO bonds with silicon atoms in the silicon-containing particles.
4. The silicon-based composite material according to claim 1, characterized in that: The pore volume of the silicon-based composite material is 0.001 cm 3 / g-0.2cm 3 / g, specific surface area is 0.1m 2 / g-50m 2 / g.
5. The silicon-based composite material according to claim 3, characterized in that: Based on 100% mass of the silicon-based composite material, the proportion of silicon element is 10wt.%-80wt.%, the proportion of oxygen element is 0wt.%-10wt.%, and the proportion of the first doping element M and the second doping element R is 0wt.%-10wt.% in total.
6. The silicon-based composite material according to claim 1, characterized in that: The porous structure of the porous carbon substrate is continuous branch-like through holes; Preferably, the pore size of the porous structure is larger than the particle size of the silicon-containing particles; Preferably, the pore size of the porous structure is 0.5nm-50nm; Preferably, the particle size of the silicon-containing particles is 0.5 nm-20 nm.
7. The silicon-based composite material according to claim 1, characterized in that: The silicon-based composite material further comprises a coating layer, and the material of the coating layer comprises an ion-conducting material and / or an electron-conducting material; Preferably, the ion-conducting material comprises at least one of a LISICON-type solid electrolyte, a NASICION-type solid electrolyte, a perovskite-type solid electrolyte, a garnet-type solid electrolyte, a sulfide solid electrolyte and a PEO-based polymer electrolyte; Preferably, the conductive electronic material includes at least one of soft carbon, hard carbon, carbon black, graphite, graphene, carbon nanotubes, and carbon fibers.
8. The silicon-based composite material according to claim 1, characterized in that: The silicon-based composite material further comprises at least one of lithium silicate, magnesium silicate, aluminum silicate, lithium aluminum silicate, lithium magnesium silicate and magnesium aluminum silicate.
9. A method for preparing the silicon-based composite material according to any one of claims 1 to 8, characterized in that: Using an inert gas as a carrier gas, introducing a silicon-containing precursor and an oxygen-containing precursor, and loading silicon-containing particles in the pores of the carbon-containing substrate by vapor deposition; Preferably, the step further comprises doping the carbon-containing substrate with a first element M; Preferably, the step further comprises doping the silicon-containing particles with a second element R; Preferably, the step further comprises coating the surface of the silicon-based composite material with an ion-conducting material and / or an electron-conducting material.
10. The preparation method according to claim 9, characterized in that: The temperature of the vapor deposition is 150°C-1000°C, and the time is 0.1h-100h; Preferably, the silicon-containing precursor includes at least one of monosilane, disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives; Preferably, the oxygen-containing precursor comprises at least one of oxygen, carbon dioxide, water vapor, methanol, ethanol, n-propanol, isopropanol, butanol, acetone and butanone.